KOMPARASI KEBIJAKAN PENDIDIKAN ISLAM DI ERA ORDE LAMA DAN ORDE BARU - Elin Pebriani Hutagalung; Zaianal Efendi Hasibuan (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
Islamic education experienced considerable development from the beginning of independence until the emergence of the old order and the new order. Therefore, the government is paying great attention to it at the moment. The purpose of this writing is to provide readers with an understanding of Islamic education policies in the Old Order and New Order eras. To achieve this goal, this writing uses literature studies from books, journals and relevant news. The research results show that Islamic education in the Old Order era began to be paid attention to, as shown by the inclusion of religious education in state and private schools, but parents and students could refuse if they objected. In the New Order era, Islamic education began to develop, with the use of the national curriculum in madrasa schools like general schools.